2022
DOI: 10.1093/tbm/ibac018
|View full text |Cite
|
Sign up to set email alerts
|

Motivating cascade testing for familial hypercholesterolemia: applying the extended parallel process model for clinician communication

Abstract: Motivating at-risk relatives to undergo cascade testing for familial hypercholesterolemia (FH) is critical for diagnosis and lifesaving treatment. As credible sources of information, clinicians can assist in family communication about FH and motivate cascade testing uptake. However, there are no guidelines regarding how clinicians should effectively communicate with probands (the first person diagnosed in the family) and at-risk relatives. Individuals and families with FH can inform our understanding of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Specifically, patients wanted to receive information that is relevant, understandable, concise, usable, appropriate, sympathetic, and available when needed and through multiple communication modes (i.e., digital technologies, print, and conversations with health care providers) [31]. Furthermore, a similar study to optimize communication with individuals with familial hypercholesterolemia found that messages stressing the health threat to relatives and their susceptibility due to heredity were important motivators for cascade testing [32]. However, a novel finding in our study was the request from probands with no living relatives for messaging showing what genetic testing could do for them.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, patients wanted to receive information that is relevant, understandable, concise, usable, appropriate, sympathetic, and available when needed and through multiple communication modes (i.e., digital technologies, print, and conversations with health care providers) [31]. Furthermore, a similar study to optimize communication with individuals with familial hypercholesterolemia found that messages stressing the health threat to relatives and their susceptibility due to heredity were important motivators for cascade testing [32]. However, a novel finding in our study was the request from probands with no living relatives for messaging showing what genetic testing could do for them.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al [ 64 ] conducted 5 focus groups with 42 participants, guided by the conceptual model of implementation research, that found the use of automated approaches to identify individuals with FH through the EMR and family communication methods including chatbots and direct contact was acceptable, appropriate and feasible methods to detect FH. Through 11 dyadic interviews and 98 survey respondents’, guidance of effective messaging to motivate cascade testing uptake for FH were suggested and include participants prioritizing messages from four key constructs (severity, susceptibility, response efficacy and self-efficacy), and clinicians could use these constructs to communicate to at-risk relatives about the importance of pursuing diagnosis via cascade testing and subsequent medication management approaches [ 65 ]. A forthcoming Campbell et al study reports on the optimization of these implementation strategies, which is currently undergoing peer review.…”
Section: Tailoring Implementation Strategiesmentioning
confidence: 99%
“…How does your family talk about FH?) (21,22). Before interviews, participants were asked to review three family communication strategies and share their feedback on how to (re)design these strategies during the interviews (e.g., How can we improve the family letter?…”
Section: Interviews and Surveysmentioning
confidence: 99%